Nutrient content and uptake of basmati rice as influenced by organic and inorganic sources of nutrients - Yadav, Komal; Yadav, Devideen; Yadav, R.B. (Annals of Agricultural Research, 2017)
Performance of organic sources i.e. vermi-compost (VC), poultry manure (PM), farm yard manure(FYM) in combination with chemical fertilizers and sole chemical fertilizers with 100% recommendeddose of fertilizers (RDF) i.e. 120:60:60 NPK kg ha–1 and 125% RDF were evaluated in terms of nutrientcontent and nutrient uptake of basmati rice at crop research centre of Sardar Vallabhbhai PatelUniversity of Agriculture and Technology, Meerut, India, during kharif - 2013 using randomizedblock design (RBD). Results revealed that highest nitrogen, phosphorus and potassium content ingrain and straw and their uptake in basmati rice were recorded with application of 125% RDFthrough inorganic source of nutrient over other treatments. The highest grain (4.56 t ha–1) andstraw yield (6.49 t ha–1) was also recorded with 125% RDF through inorganic source of nutrient butit was statistically similar to the treatment containing 50% RDF through inorganic sources + 50%through PM.